Advances in cancer diagnosis and treatment: A review of CONVERAY and COXIRIS radiation technologies - Current state and future directions - Figueroa, Rodolfo G. (2025)
This short review showcases two innovative technological advances, culminating in more than a decade of research into advanced oncology devices: CONVERAY and COXIRIS. In this context, it is essential to evaluate how these technologies can optimize performance in specific applications. CONVERAY is a convergent beam radiotherapy system, adaptable to linear particle accelerators (LINACs), designed to deliver a focused megavoltage photon or electron beam to a precise tumor location. This innovative approach achieves depth-dose peaks comparable to proton therapy, optimizing therapeutic efficacy while minimizing exposure to surrounding healthy tissues. Following this line of analysis, the results obtained through advanced simulations are examined. Notably, CONVERAY is compatible with ultra-high dose rate FLASH technology, enabling faster and less toxic treatments. Its implementation requires minimal LINAC modifications, preserving precise physical dimensions and mechanical, electrical, magnetic, vacuum, and shielding conditions. These findings allow for a more detailed exploration of practical implications in clinical environments. Complementing CONVERAY, COXIRIS is a confocal system designed for theragnostic applications utilizing X-ray fluorescence (XRF) in specific biomarkers. This innovative device enables the detection of fluorescent radiation in biomarkers at depths of up to 10 cm, providing detailed tumor characterization. Its confocal configuration facilitates simultaneous therapeutic interventions, integrating real-time detection and treatment for precise oncological management. Finally, key aspects that may influence future implementations and clinical applications are highlighted. COXIRIS represents a significant advancement toward an integrated and efficient cancer treatment solution, harmonizing diagnosis and therapy. Building upon the presented findings, these technologies offer a pathway toward transforming cancer treatment strategies. In summary, both CONVERAY and COXIRIS technologies, currently in the prototype phase, represent substantial breakthroughs in radiotherapy and oncological theragnosis, holding promise as pivotal tools for enhancing precision and efficacy in future cancer treatments. Their innovative designs and integrated approaches position these technologies at the forefront of oncological care, poised to transform treatment paradigms and improve patient outcomes.